2020
DOI: 10.1093/nc/niaa017
|View full text |Cite
|
Sign up to set email alerts
|

Brain network motif topography may predict emergence from disorders of consciousness: a case series

Abstract: Neuroimaging methods have improved the accuracy of diagnosis in patients with disorders of consciousness (DOC), but novel, clinically translatable methods for prognosticating this population are still needed. In this case series, we explored the association between topographic and global brain network properties and prognosis in patients with DOC. We recorded high-density electroencephalograms in three patients with acute or chronic DOC, two of whom also underwent an anesthetic protocol. In these two cases, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Similar to anatomically-defined structural motifs which form fundamental building blocks of neural circuits 1 , 67 , 68 , functional motifs, which are defined by correlated neural activities, represent elementary information processing components of a functional network 69 . Although extensive over-representation of certain network motifs such as feedforward loop is found mostly in anatomical networks 1 , 52 , 67 , 70 , functional motifs (especially triplets) also have been discovered to reflect the level of consciousness 71 , 72 , accurately predict neural activity 73 , encode global topological information 74 , and exhibit coupling with anatomical connections 75 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to anatomically-defined structural motifs which form fundamental building blocks of neural circuits 1 , 67 , 68 , functional motifs, which are defined by correlated neural activities, represent elementary information processing components of a functional network 69 . Although extensive over-representation of certain network motifs such as feedforward loop is found mostly in anatomical networks 1 , 52 , 67 , 70 , functional motifs (especially triplets) also have been discovered to reflect the level of consciousness 71 , 72 , accurately predict neural activity 73 , encode global topological information 74 , and exhibit coupling with anatomical connections 75 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found reduced white matter fibre connections 10 and functional connections 71 between several regions within the DMN in DOC patients. A recent case study 72 showed that motif configurations within the DMN can predict the clinical recovery of DOC patients. We inferred that the three-node connection patterns within and between the DMN might be essential to the maintenance of conscious activity.…”
Section: Discussionmentioning
confidence: 99%
“…The key points for improving the prognosis were early diagnosis and prompt therapy, consequently, the patient was diagnosed as having hypoactive DOC based on CRS‐R and MBT (Pignat JM et al, 2016). At present, there are advanced diagnostic techniques for DOC, for example, the brain network motif topography, functional MRI (fMRI), and processed EEG (pEEG) (Nadin D, et al, 2020; Bernat J L. 2009). It is worth mentioning that transcranial magnetic stimulation‐ electroencephalogram (TMS‐EEG) has been preliminarily applied to discriminant consciousness under various physiological (sleep), pharmacological (anesthesia), pathological (coma, vegetative state, etc.)…”
Section: Discussionmentioning
confidence: 99%